PENGEMBANGAN PENDIDIKAN ISLAM: MEMBENTUK GENERASI UNGGUL MELALUI PENDIDIKAN BERBASIS AL QUR’AN DAN HADIS - Y Satria Hafizil Khalil; Fathurrahman Muhtar (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2024)
This article aims to discuss the importance of education in forming a superior generation based on the values ​​of the Koran and Hadith. Education has a vital role in developing knowledge and human potential. Through education, individuals can explore and optimize their abilities to face life's challenges and contribute positively to society. This research uses qualitative methods with a library research research approach, and examines various interpretations of the Al-Qur'an and Hadith as well as the opinions of Muslim scholars regarding the goals of education. The results of this research show that education must be based on faith and piety, developing humans to become obedient servants of Allah and responsible caliphs on earth. Education in Islam not only emphasizes cognitive development, but also strengthening character and commendable morals. Education based on the Al-Qur'an and Hadith has a role in forming a generation that is strong, has morals, and is able to carry out its role as a trustworthy and responsible leader. This research underlines that education must have clear and directed goals, and be supported by appropriate strategies to produce individuals who are academically and character competent. With a comprehensive approach, Islamic education can develop superior human beings and can have a positive impact on the people and the country.